Stable Angina Treatment Strategies and Current Practices in Lahore, Pakistan: A Cross-Sectional Analysis (International Current Pharmaceutical Journal, 2016)
The purpose of the study was to analyze the prescription trends in the treatment of stable angina and to identify the therapeutic agents being prescribed majorly In Pakistan and to analyze that whether the current prescription patterns are in accordance with evidence based guidelines. A concurrent type of study was conducted from 24-01-2015 to 24-04-2015, through collection of data from prescriptions of patients suffering from stable angina in public sector hospitals of Lahore Pakistan. Data observations from the total 200 prescriptions collected from the hospitals of Lahore graphically demonstrate the trends of drug classes per prescription. The study identified that in the treatment of stable angina Antiplatelet are the most frequently prescribed drug class in Lahore and adjacent areas. Followed by CCBs on 2nd rank and nitrates on 3rd rank, ACE inhibitors and ARBs on 4th number, after which statins occupy the 5th position, lastly comes the position of beta blocker i.e. 6th and diuretics are the least prescribed class. The anti-platelet blocker drugs were the most prescribed drug class in the management of chronic stable angina followed by calcium channel and vasodilators occupying the second and third rank respectively. The study also revealed that men are 1.5 times more vulnerable to the development of angina than the females. The study is also showing concrete evidence that there is strong need to follow guidelines for proper treatment.Ahmed et al., International Current Pharmaceutical Journal, December 2016, 6(1): 1-5http://www.icpjonline.com/documents/Vol6Issue1/01.pdf